2015
DOI: 10.1016/j.cognition.2014.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Array heterogeneity prevents catastrophic forgetting in infants

Abstract: Working memory is limited in adults and infants. But unlike adults, infants whose working memory capacity is exceeded often fail in a particularly striking way: they do not represent any of the presented objects, rather than simply remembering as many objects as they can and ignoring anything further (Feigenson & Carey 2003, 2005). Here we explored the nature of this “catastrophic forgetting,” asking whether stimuli themselves modulate the way in which infants’ memory fails. We showed 13-month old infants obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 76 publications
(128 reference statements)
2
35
0
Order By: Relevance
“…In contrast, when items are presented sequentially one after the other, the network retains a buffer of the most recent items. These computational results fit well with the observation that participants in WM experiments tend to process items sequentially even when they are presented simultaneously (e.g., Liu & Becker, 2013;Vogel et al, 2006; but see Mance et al, 2012), as this might protect them from catastrophic interference (though infants might show catastrophic interference; Feigenson, 2005;Zosh & Feigenson, 2015). Be that as it might, Sengupta et al's (2014) and Knops et al's (2014) results show that mutual inhibition among neurons can lead to finite memory capacity limitations.…”
Section: Dennis and Humphreys (2001)supporting
confidence: 82%
See 1 more Smart Citation
“…In contrast, when items are presented sequentially one after the other, the network retains a buffer of the most recent items. These computational results fit well with the observation that participants in WM experiments tend to process items sequentially even when they are presented simultaneously (e.g., Liu & Becker, 2013;Vogel et al, 2006; but see Mance et al, 2012), as this might protect them from catastrophic interference (though infants might show catastrophic interference; Feigenson, 2005;Zosh & Feigenson, 2015). Be that as it might, Sengupta et al's (2014) and Knops et al's (2014) results show that mutual inhibition among neurons can lead to finite memory capacity limitations.…”
Section: Dennis and Humphreys (2001)supporting
confidence: 82%
“…As a result, it is unclear to what extent Knops et al's (2014) subitizing response profile reflects voxels that are involved in small number processing as opposed to voxels that are not involved in small number processing, and that only support large number processing instead. or when they are made more distinctive, infants also succeed with a total of 4 objects (e.g., Feigenson & Halberda, 2008;Rosenberg & Feigenson, 2013;Zosh & Feigenson, 2015).…”
Section: The Role Of Interference In Other Cognitive Capacity Limitatmentioning
confidence: 99%
“…The results of Zosh and Feigenson (2015) favor the latter account. Previous work combined with that of their 2015 paper showed that when the objects are all identical, fewer of them are retrieved than when the objects differ, suggesting that infants process the differences between objects.…”
Section: Development Of Working Memory Capacity In Infancymentioning
confidence: 65%
“…The best performance has been obtained when the items are all different (Zosh & Feigenson, 2015). Infants 13-months old will search for the first two items and often will search for a third item.…”
Section: Development Of Working Memory Capacity In Infancymentioning
confidence: 99%
“…However, at least in infancy, some cognitive abilities such as number processing do show catastrophic performance limitations. For example, while infants reliably choose three over one food item, they are unable to choose between four and one food item; the most common explanation is that the number system used to process small numbers up to three is incompatible with the system used to process large numbers beyond three (e.g., Feigenson & Carey, ; Feigenson, Carey, & Hauser, ; Zosh & Feigenson, ). Furthermore, in line with long‐standing theorizing that our cognitive abilities might suffer from a general capacity limit (e.g., Cowan, ; Miller, ), this small number system might be related or even identical to working memory (WM) (Cowan, ; Piazza, Fumarola, Chinello, & Melcher, ), which also has important capacity limitations (e.g., Cowan, ; Fukuda, Vogel, Mayr, & Awh, ; Luck & Vogel, ; Vogel, Woodman, & Luck, ).…”
Section: Introductionmentioning
confidence: 98%